Expert validation of teacher's academic workload assessment tool for secondary schools - Wan Mohd Khairi, Wan Ibrahim; Azim Azuan, Osman; Suhaidah, Hussain (Global Academic Excellence (M) Sdn Bhd (GAE), 2025)
The academic workload of teachers is an important factor to assess, as it significantly influences both educational outcomes and teacher well-being. This study was conducted to validate an instrument, through expert consultation, for measuring teachers’ workload in secondary schools. A review of the literature highlights that excessive workload can contribute to teacher burnout, declining job satisfaction, and adverse effects on students’ academic achievement. These challenges are further intensified by the modernization of the education system and increasing administrative demands, which add to the complexity of teachers’ professional responsibilities. The current study aimed to authenticate a tool, via expert validation, specifically created to assess the workload of teachers in secondary schools, with a focused consideration of its ramifications for research activities. To ensure the instrument’s validity, a panel of experts in educational leadership, curriculum, and teacher professional development evaluated its clarity, relevance, and comprehensiveness. The Content Validity Index (CVI) and inter-rater agreement (IRA) methods were employed to determine the level of consensus among experts. The results showed that the instrument achieved a high level of content validity across all domains, confirming its appropriateness for assessing teachers’ academic workload in the secondary school context. However, a small number of items required revision based on expert recommendations. This validated tool provides a reliable foundation for future empirical research, policy formulation, and administrative practices aimed at optimizing workload management. By offering a systematic approach to evaluating academic workload, the instrument contributes to improving teacher well-being, supporting professional development, and promoting more effective and sustainable educational practices.